PEMANFAATAN HASIL BUDIDAYA MAGGOT Hermetia illucents SEBAGAI BAHAN PAKAN ALTERNATIF IKAN DI KELOMPOK WANITA TANI “MAKMUR BERKAH” DESA KUTASARI KABUPATEN BANYUMAS - Setiyono, Eko; Sukmaningrum, Sri; Hana, Hana; Simagunsong, Tohap; Susatyo, Priyo; Sugiharto, Sugiharto; Atang, Atang (Jurnal Abdi Insani, 2024)
The women's farmer group (KWT) "Makmur Berkah" is located in Kutasari Village, Baturraden District, Banyumas Regency, which has activities managing village-owned agricultural land and managing fish farming ponds. Fish farming carried out by members varies, for example, tilapia, gourami, carp, tilapia, pomfret and catfish. Fish farming efforts aim to improve the resilience and welfare of member families, but these activities are still secondary and have not been managed properly and the main problem faced is the provision of fish feed. This community service aims to provide skills in training in making alternative fish feed based on Hermetia illucents maggots. The methods used in this community service are program socialization, material presentation, post-harvest handling training for maggots, making feed formulations, making alternative feed in the form of pellets for fish feed, mentoring, and program evaluation. To determine understanding of the program, an evaluation was carried out in the form of providing a pre-test and post-test. In addition, an evaluation was also carried out to determine changes in partner behavior and the impact of making demonstration plots on partners. The results of community service activities are that the KWT group is enthusiastic about participating in socialization, listening to materials and discussions. Then the KWT group was able to make a fish pellet feed formulation and print fish pellets from Hermentia illusens larvae flour. Thus, it can be concluded that the activities provided were able to equip KWT in producing alternative fish feed based on maggots.